2021
DOI: 10.3390/nano11061555
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Metal Oxide Nanofibers and Their Conductometric Gas Sensor Application. Part 2: Gas Sensors and Their Advantages and Limitations

Ghenadii Korotcenkov

Abstract: Electrospun metal oxide nanofibers, due to their unique structural and electrical properties, are now being considered as materials with great potential for gas sensor applications. This critical review attempts to assess the feasibility of these perspectives. This article discusses approaches to the manufacture of nanofiber-based gas sensors, as well as the results of analysis of the performances of these sensors. A detailed analysis of the disadvantages that can limit the use of electrospinning technology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 372 publications
0
15
0
1
Order By: Relevance
“…Experimental analysis, as well as theoretical measurement, verified that electrospinning nanofibers are extremely beneficial for trapping airborne contaminants [ 35 , 36 , 37 ]. Figure 3 a–f shows the cold field emission type scanning electron micrographs of the active molecular films of chrysin, baicalein, scutellarein, genistein, quercetin, and baicalin after sampling, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental analysis, as well as theoretical measurement, verified that electrospinning nanofibers are extremely beneficial for trapping airborne contaminants [ 35 , 36 , 37 ]. Figure 3 a–f shows the cold field emission type scanning electron micrographs of the active molecular films of chrysin, baicalein, scutellarein, genistein, quercetin, and baicalin after sampling, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Other limitations of electrospun nanofibers are their brittleness and inability to fully adhere to the substrate surface after coating with metal oxide. Nanofibers containing metal oxide can become fragile and break after calcination [99]. This fragility will especially limit the use of a flexible biosensor [100].…”
Section: Current Limitations and Future Applicationsmentioning
confidence: 99%
“…Studies have shown that the unique properties of such structures make it possible to optimize the main parameters of gas sensors, such as sensitivity and rate of response [ 1 , 2 , 3 , 4 , 5 ]. In [ 5 , 6 , 7 ], a detailed consideration of the manufacturing features of gas sensors based on 1D and 2D structures and nanofibers was carried out, and the advantages and disadvantages of using such structures in this area were shown. In this article, we will continue the analysis of nanomaterials suitable for the development of gas sensors and focus on the consideration of porous 2D structures.…”
Section: Introductionmentioning
confidence: 99%